Respon Paulus Atas Gaya Hidup Jemaat Korintus: Analisa Retoris Terhadap 2 Korintus 6:11-7:1 - Rimun, Robinson; Lumbantobing, Tomson (Ambassadors: Jurnal Teologi dan Pendidikan Kristiani, 2021)
The rhetorical method is one of the prominent literary styles in the first century AD. Paul, one of the main writers of the New Testament books, used this method in the various arguments, including in 2 Corinthians. Hermeneutic studies that focus on the possibility of rhetorical analysis and how this method is applied in interpreting 2 Corinthians 6:11-7:1 are the main focus of this paper. This study found a persuasive style and rhetorical argumentative discourse in Paul's writing from the various data collected and Paul's analyzed and interpreted arguments. The structure and technique of Paul's argumentative approach and his advice to the Corinthian church is a combination of rhetorical elements and the uniqueness of Paul's writing style. The lifestyle of the Corinthian church that emerged as a result of the church's attitude of openly accepting unbelievers and their improper lifestyle caused the church to be polarized in groups and experienced spiritual decadence.